2020
DOI: 10.1111/liv.14313
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of elbasvir/grazoprevir for 8 or 12 weeks for hepatitis C virus genotype 4 infection: A randomized study

Abstract: Abbreviations: AE, adverse event; ALT, alanine aminotransferase; APaT, all participants as treated; APRI, aspartate aminotransferase to platelet ratio index; ART, antiretroviral therapy; AST, aspartate aminotransferase; DAA, direct-acting antiviral; EBR/GZR, elbasvir/grazoprevir; FAS, full analysis set; GT, genotype; HBsAg, hepatitis B surface antigen; LLOQ, lower limit of quantification; mFAS, modified full analysis set; NS5A, non-structural protein 5A; RAS, resistance-associated substitutions; SVR, sustained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…Similarly, in a partially randomized, open‐label multicenter study conducted in France (NCT03111108), GT4 treatment‐naive individuals with mild fibrosis can also be treated effectively with an 8‐week regimen 34 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a partially randomized, open‐label multicenter study conducted in France (NCT03111108), GT4 treatment‐naive individuals with mild fibrosis can also be treated effectively with an 8‐week regimen 34 …”
Section: Discussionmentioning
confidence: 99%
“…1 Direct-acting antivirals (DAAs) have revolutionized HCV therapy, with sustained virological response (SVR) rates of over 95% for the most common genotypes regardless of comorbidities. [2][3][4][5][6] The achievement of an SVR by DAAs in patients with chronic HCV infection also implies substantial improvements in liver histological findings, liver function, gastroesophageal varices grades, HCC complication risk, and more in the clinical setting. [7][8][9] HCV hijacks hepatic lipid pathways in multiple aspects of its life cycle, starting with attachment of the HCV particle to lowdensity lipoprotein (LDL) and high-density lipoprotein (HDL) receptors of scavenger receptor class B type 1 and ensuing expression regulation, [10][11][12] all of which suggest a close association between HCV infection and serum lipid levels.…”
Section: Introductionmentioning
confidence: 99%
“…In chronic HCV infection, the C-WORTHY trial showed that higher SVR12 rates were achieved in patients treated with 12-week versus 8-week grazoprevir/elbasvir. 17 Nevertheless, more recent clinical trials evaluating 8-week grazoprevir/elbasvir have demonstrated high SVR in HCV genotype 1b or 4 infected patients with liver fibrosis levels at METAVIR F0-F2 25,26 or in genotype 1b when plasma HCV-RNA is low. 27 Given that MSM recently acquiring HCV are unlikely to have severe liver fibrosis 28 , 8-week duration of grazoprevir/elbasvir could be sufficient for treating acute HCV.…”
Section: Discussionmentioning
confidence: 99%